Likelihood ascent search augmented sphere decoding receiver for MIMO systems using M‐QAM constellations. Issue 22 (26th February 2021) - Ullah, Arif; Abbas, Ziaul Haq; Zaib, Alam; Ullah, Irfan; Muhammad, Fazal; Idrees, Muhammad; Khattak, Shahid
Abstract : MIMO systems employing sphere decoding (SD) algorithm are known to achieve near maximum likelihood (ML) performance at a reduced complexity by restricting the candidate search space to a sphere of a certain radius. The performance of SD depends on the precise estimation of its soft output. In this paper, a low complexity modified Likelihood Ascent Search (LAS) algorithm is proposed to be used within a SD receiver in order to precisely estimate the counter‐hypothesis for its winner candidates. The LAS algorithm is modified to search for the best counter‐hypothesis in only one‐half of the signal lattice thereby improving the performance of MIMO receiver. Our results challenge the popular perception that for a SD receiver a large number of candidates within the search sphere is essential for good performance. Instead, it is shown that accurate estimation of the counter‐hypothesis is equally important and in fact, the performance of the proposed augmented SD receiver with only single candidate approaches that of a classical SD with multiple candidates. Bit error rate performance of the proposed method when compared with the existing research works on soft output generation for the same number of candidates shows that our proposed method outperforms them by upto 3 dB.